Experiments and theory for two grids turbulence - Schulz,Harry E. (2006)
Turbulence generated by a pair of oscillating grids in a water tank is investigated using the digital particle image velocimetry technique. Vertical and horizontal components of fluctuating velocities are measured. Experimental profiles of the turbulent kinetic energy k, and the energy dissipation rate, xi, obtained from the fluctuating velocities, are presented and compared with theoretical predictions. Other properties of interest, such as the length scale and the turbulent viscosity, obtained in the present study, are also reported. The turbulence generated with the pair of grids may be classified as "nearly isotropic" and theoretically the flow may be analyzed using the k-epsilon model. The experimental data agree well with the theoretical predictions. Also data of different sources found in literature, for pairs of vibrating grids, are compared with the present experimental results and theoretical predictions, showing good agreement. The studies conducted at the Laboratory of Environmental Hydraulics from the Department of Hydraulics and Sanitary Engineering, EESC/USP, permits to affirm that "double oscillating grids" turbulence can be viewed as nearly isotropic.